Effect of Renewable Energi on CO2 Emissions in BRICS Countries - Aubin Simon Mandimby (PT Mattawang Mediatama Solution, 2024)
This paper analyzes the effect of renewable energy on carbon emissions in the BRICS countries (Brazil, Russia, India, China, and South Africa) from 1990 to 2020. Using the PMG panel ARDL approach to estimate the model. The findings indicate that renewable energy positively reduces carbon emissions in both the short and long run. However, industrialization and economic growth have a negative effect on carbon emissions reduction in both the short and long run. These results demonstrate the positive impact of renewable energies in reducing carbon emissions in BRICS countries. The study recommends that these countries promote renewable energies to meet their energy needs and reduce carbon emissions.